Formation of a large number of conidia - Akihito Kana-Uchi; Tadako Murayama (Fungal Genetics Reports, 1996)
The addition of cotton to the medium in flasks can result in a significant increase in the number of conidia from Neurospora crassa strains (wild type and mutants).